Tanshinone IIA: a Chinese herbal ingredient for the treatment of atherosclerosis - Yang, Chunkun; Mu, Yanguang; Li, Shuanghong; Zhang, Yang; Liu, Xiaoyuan; Li, Jun (Frontiers in Pharmacology, 2023)
Tanshinone IIA (Tan IIA) is a fat-soluble compound extracted from Salvia miltiorrhiza, which has a protective effect against atherosclerosis (AS). Tan IIA can inhibit oxidative stress and inflammatory damage of vascular endothelial cells (VECs) and improve endothelial cell dysfunction. Tan IIA also has a good protective effect on vascular smooth muscle cells (VSMCs). It can reduce vascular stenosis by inhibiting the proliferation and migration of vascular smooth muscle cells (VSMCs), and improve the stability of the fibrous cap of atherosclerotic plaque by inhibiting apoptosis and inflammation of VSMCs. In addition, Tan IIA inhibits the inflammatory response of macrophages and the formation of foam cells in atherosclerotic plaques. In summary, Tan IIA improves AS through a complex pathway. We propose to further study the specific molecular targets of Tan IIA using systems biology methods, so as to fundamentally elucidate the mechanism of Tan IIA. It is worth mentioning that there is a lack of high-quality evidence-based medical data on Tan IIA treatment of AS. We recommend that a randomized controlled clinical trial be conducted to evaluate the exact efficacy of Tan IIA in improving AS. Finally, sodium tanshinone IIA sulfonate (STS) can cause adverse drug reactions in some patients, which needs our attention.